HOPE AND SACRIFICE IN THE SHORT STORY 'THE LAST LEAF' BY O. HENRY - Aisha, Shazfa Q.; Mahi M. Hkikmat, Mahi M. (Saksama: Jurnal Sastra, 2024)
This research explores the themes of hope and sacrifice using William Wordsworth's romanticism theory to analyze the themes of hope and sacrifice in O. Henry's short story The Last Leaf. An ill young woman named Johnsy believes she will die when the last leaf on the ivy vine outside her window falls in this short story. The main characters of the story are her close friend Sue and their elderly neighbor Behrman, an artist who eventually sacrifices his life to keep Johnsy from losing hope by painting a realistic leaf. This research looks at Romanticism, which emphasizes emotion and nature, shaped the story's structure and development of characters in The Last Leaf. This research examines how the characters' emotional experiences connect with Romantic ideals through a textual analysis of the short story. Based on the findings, it can be considered that Wordsworth's Romanticism is reflected in The Last Leaf, which portrays the remarkable act of creating art, the strength of hope, and human sacrifice. Behrman's last act of kindness, painting the leaf, is seen as a romantic gesture that exceeds reality and captures the hope that is present in the hopelessness of winter. The research concludes that O. Henry's short story represents Romantic ideals and emphasizes the capacity for selflessness in the human spirit.